Efficacy of newer insecticides against Spodoptera litura in sunflower (Helianthus annuus L.): Efficacy of newer insecticides against Spodoptera litura in sunflower (Helianthus annuus L.) - S S LAKSHMAN; M K GODKE; H BASAPPA (Journal of Oilseeds Research, 2017)
Field experiment was conducted during rabi-summer season of 2014-15 and 2015-16 to evaluate the efficacy of certain newer chemical insecticides (flubendiamide 480SC, spinosad 48SC, thiodicarb 75WP, thiodicarb 80DF, novaluron 10EC) with conventional insecticides (dichlorvos 76EC and chlorpyriphos 20EC) against tobacco caterpillar, Spodoptera litura in sunflower. Results revealed that the maximum percentage of larval reduction and defoliation was in flubendiamide 480SC @ 150ml/ha followed by spinosad 48SC @ 150ml/ha. Highest seed yield were recorded in flubendiamide (1950 and 1825 kg/ha) followed by spinosad (1875 and 1740 kg/ha) and thiodicarb 75WP (1785 and 1700 kg/ha) as against 1500 and 1400 kg/ha in untreated control during 2014-15 and 2015-16, respectively. The maximum cost-benefit ratio of 1:2.1 and 1:2.05 was obtained with flubendiamide during 2014-15 and 2015-16, respectively.